Key determinants for high-alloyed cast irons for mechanical engineering - Pacha-Gołębiowska, Halina; Piekarska, W. (Zielona Góra: Uniwersytet Zielonogórski)
This work presents the factors determining cast iron, and particularly austenitic high-alloy cast iron as a construction material, which is ranked among the leading casting alloys of iron with carbon, mainly due to its very good service properties, which makes it dedicated as a material for automotive castings, pipe and fitting castings and components resistant to elevated temperatures, corrosion and abrasive wear.
Keywords: alloyed cast iron; wear; machining conditions; alloying additives; coatings; roughness